Targeting Non-coding RNA in Vascular Biology and Disease - Hung, John; Miscianinov, Vladislav; Sluimer, Judith C.; Newby, David E.; Baker, Andrew H. (Frontiers in Physiology, 2018)
Only recently have we begun to appreciate the importance and complexity of the non-coding genome, owing in some part to truly significant advances in genomic technology such as RNA sequencing and genome-wide profiling studies. Previously thought to be non-functional transcriptional “noise”, non-coding RNAs are now known to play important roles in many diverse biological pathways, not least in vascular disease. Whilst micro RNAs (miRNA) are known to regulate protein-coding gene expression principally through mRNA degradation, long non-coding RNAs (lncRNAs) can activate and repress genes by a variety of mechanisms at both transcriptional and translational levels. These versatile molecules, with complex secondary structures, may interact with chromatin, proteins and other RNA to form complexes with an array of functional consequences. A body of emerging evidence indicates that both classes of non-coding RNAs regulate multiple physiological and pathological processes in vascular physiology and disease. Whilst dozens of miRNAs are now implicated and described in relative mechanistic depth, relatively fewer lncRNAs are well described. However, notable examples include ANRIL, SMILR and SENCR in vascular smooth muscle cells; MALAT1 and GATA-6S in endothelial cells; and mitochondrial lncRNA LIPCAR as a powerful biomarker. Due to such ubiquitous involvement in pathology and well-known biogenesis and functional genetics, novel microRNA-based therapies and delivery methods are now in development, including some early stage clinical trials. Although lncRNAs may hold similar potential, much more needs to be understood about their relatively complex molecular behaviours before realistic translation into novel therapies. Here, we review the current understanding of the mechanism and function of non-coding RNA, focusing on microRNAs and long non-coding RNAs in vascular disease and atherosclerosis. We discuss existing therapies and current delivery methods, emphasising the importance of miRNAs and lncRNAs as effectors and biomarkers in vascular pathology.